2005
DOI: 10.1152/ajpheart.00626.2004
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-induced defects in renal oxygenation: role of oxidative stress

Abstract: We tested the hypothesis that superoxide anion (O(2)(-).) generated in the kidney by prolonged angiotensin II (ANG II) reduces renal cortical Po(2) and the use of O(2) for tubular sodium transport (T(Na):Q(O(2))). Groups (n = 8-11) of rats received angiotensin II (ANG II, 200 ng.kg(-1).min(-1) sc) or vehicle for 2 wk with concurrent infusions of a permeant nitroxide SOD mimetic 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl (Tempol, 200 nmol.kg(-1).min(-1)) or vehicle. Rats were studied under anesthesia with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
188
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(198 citation statements)
references
References 61 publications
9
188
1
Order By: Relevance
“…Of note, oxidative stress per se aggravates hypoxia in the kidney. Oxidative stress reduces the efficiency of oxygen use by disturbing mitochondrial respiration, thereby contributing to the resulting hypoxia in the kidney (30,49). The consumption of vasodilatory nitric oxide by oxidative stress can also result in a decrease in kidney blood flow, further aggravating renal hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, oxidative stress per se aggravates hypoxia in the kidney. Oxidative stress reduces the efficiency of oxygen use by disturbing mitochondrial respiration, thereby contributing to the resulting hypoxia in the kidney (30,49). The consumption of vasodilatory nitric oxide by oxidative stress can also result in a decrease in kidney blood flow, further aggravating renal hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, angiotensin II reduced the efficiency of renal oxygen usage in tubular sodium transport, resulting in a decrease in oxygen tension throughout the cortex. Tempol blunted all these effects of angiotensin II (55). Further, Adler and Huang showed that NO bioavailability in SHR is impaired due to an angiotensin II-mediated increase in superoxide production in association with enhanced expression of NADPH oxidase components (56).…”
Section: Oxidative Stressmentioning
confidence: 94%
“…Kidneys of the spontaneously hypertensive rat (SHR), which characteristically undergo oxidative stress, revealed enhanced oxygen usage relative to tubular sodium transport and lower intrarenal pO 2 (45). Amelioration of oxidative stress improved renal oxygenation in a model of diabetic nephropathy (46) and in the angiotensin II continuous infusion model (47). The same oxidative stress-related mechanism may cause tubulointerstitial hypoxia in the aging kidney (48).…”
Section: Oxidative Stress and Inefficient Cellular Respirationmentioning
confidence: 99%